Reproductive strategy of the shrimp Nematopalaemon schmitti (Decapoda, Caridea, Palaemonoidea) on the southeastern coast of Brazil - Pereira, Rafaela Torres; Almeida, Ariádine Cristine; Teixeira, Gustavo Monteiro; Bueno, Alessandra Angélica De Pádua; Fransozo, Adilson (Sociedade Brasileira de Carcinologia, 2017)
Abstract The goal of this study was to evaluate the reproductive investment (RI) and the fecundity of the shrimp Nematopalaemon schmitti (Holthuis, 1950), caught by trawling in the southeastern Brazilian coast in 2008, 2009 and 2011. The carapace length (CL) of ovigerous females was measured and the development stage of their ovaries and embryos were analyzed. A significant relationship was observed between the female body and embryo weights (Linear regression: r² = 0.26, F = 20.77, P < 0.0001, Ln BDW = 0.92. Ln FBDW - 2.24) and between number of embryos and CL (Linear regression; stage I: r² = 0.38, F = 36.15, P < 0.0001; stage II: r² = 0.34, F = 14.10, P < 0.001), but not between the RI and CL (ANOVA: F = 0.47, df = 7, P = 0.85). Association of the changes in embryo development and ovarian maturation of ovigerous females was tested. Females with rudimentary ovaries predominantly showed embryos in stage I (early development) and females with developed ovaries only showed embryos in stage II (final development), showing synchrony between the development of both, thus supporting the hypothesis of a continuous reproductive cycle for N. schmitti in the region. Such information is fundamental for understanding the reproductive biology of these crustaceans, as well as other caridean shrimps, in order to promote the maintenance and preservation of natural stocks.
Keywords: Crustacea; fecundity; ovary development; reproductive investment; Western Atlantic